Is central dogma a global property of cellular information flow? - Piras, Vincent; Tomita, Masaru; Selvarajoo, Kumar (Frontiers in Physiology, 2012)
The central dogma of molecular biology has come under scrutiny in recent years. Here, we reviewed high-throughput mRNA and protein expression data of Escherichia coli, Saccharomyces cerevisiae, and several mammalian cells. At both single cell and population scales, the statistical comparisons between the entire transcriptomes and proteomes show clear correlation structures. In contrast, the pair-wise correlations of single transcript to protein show nullity. These data suggest that the organizing structure guiding cellular processes is observed at omics-wide scale and not at single molecule level. The central dogma, thus, globally emerges as an average integrated flow of cellular information.